Hydroxychloroquine desensitization, an effective method to overcome hypersensitivity—a multicenter experience. (April 2018) - Tal, Y; Maoz Segal, R; Langevitz, P; Kivity, S; Darnizki, Z; Agmon-Levin, N
Hydroxychloroquine (HCQ) is widely used to treat autoimmune/rheumatic diseases such as systemic lupus erythematosus (SLE). The immune modulation effects of HCQ have been highlighted as beneficial for maintaining remission of SLE as well as ameliorating skin, joint and other manifestations. Moreover, HCQ exposure for prolonged periods as well as during pregnancy is considered safe, therefore it is recommended for the vast majority of SLE patients. Although HCQ therapy requires follow-up by a specialist, its most common side effects are mild gastrointestinal disturbances, sensitivity to light and skin rashes. Of these side effects, hypersensitivity skin reactions have been suggested to play a role in reduced compliance to HCQ therapy. In the current study we present a two-stage HCQ desensitization protocol that was successfully implemented among 12 out of 13 patients. We exhibit that prolonged HCQ oral desensitization is an effective method for overcoming mild to moderate late hypersensitivity reactions and thoroughly address possible mechanisms of action.